2020
DOI: 10.1002/2211-5463.13012
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibition modulates the senescence‐associated secretory phenotype (SASP) in oral keratinocytes

Abstract: Senescent cells accumulate in different organs and develop a senescence-associated secretory phenotype (SASP), associated with the development of age-related pathologies. The constitution of the SASP varies among cell types and with the method of senescence induction; nevertheless, there is substantial overlap among SASPs, especially the presence of pro-inflammatory cytokines such as IL-1, IL-1, IL-6 and IL-8. These cytokines are highly conserved among SASPs and are implicated in the development of several c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…However, senescent cells secrete an array of proteins that have important functions in age-related diseases and cancers, known as the senescence-associated secretory phenotype (SASP) [21]; recent data suggests that senescent keratinocytes secrete some SASP factors [22] and metabolites in vitro and, in mouse models of epidermal SCC, in vivo [23,24]. Therefore, LR MPPOL keratinocytes may well have a tumour-promoting role in the pre-cancerous field of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, senescent cells secrete an array of proteins that have important functions in age-related diseases and cancers, known as the senescence-associated secretory phenotype (SASP) [21]; recent data suggests that senescent keratinocytes secrete some SASP factors [22] and metabolites in vitro and, in mouse models of epidermal SCC, in vivo [23,24]. Therefore, LR MPPOL keratinocytes may well have a tumour-promoting role in the pre-cancerous field of OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Wang et al (2019) reported that fibroblast growth factor receptor (FGFR) inhibitor resistance in lung cancer is initially mediated by the cancer cell secretome activating STAT3 signalling; however, they also showed that this resistance could be enhanced via interactions with both fibroblasts and macrophages [74]. Rho-associated protein kinase (ROCK) inhibitors have recently been reported to improve chemotherapy delivery and reduce metastases in cancers such as pancreas and breast [75][76][77]. Interestingly, Niklander et al (2020) found that the ROCK inhibitor Y-27632 could decrease activity of several factors within the pro-inflammatory SASP, without altering cell cycle arrest in oral dysplastic keratinocytes [78].…”
Section: Accepted Articlementioning
confidence: 99%
“…Rho-associated protein kinase (ROCK) inhibitors have recently been reported to improve chemotherapy delivery and reduce metastases in cancers such as pancreas and breast [75][76][77]. Interestingly, Niklander et al (2020) found that the ROCK inhibitor Y-27632 could decrease activity of several factors within the pro-inflammatory SASP, without altering cell cycle arrest in oral dysplastic keratinocytes [78]. The authors show that this is mediated by IL-1 inhibition from Y-27632, which in turn regulated the secretion of protumourigenic SASP components such as IL-6 and IL-8 [78].…”
Section: Accepted Articlementioning
confidence: 99%
“…This phenotype results from the downregulation of the essential cell cycle proteins Cyclin A, CKS1 and CDK1 [53] . Therefore, ROCK inhibition could open up a new spectrum for the removal of cellular senescence [ 32 , 54 , 55 ]. The NF-κB system is an evolutionarily conserved signaling pathway triggered by immune activation and various external and internal warning signs associated with senescence and the aging process, such as oxidative and genotoxic stress [56] .…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype results from the downregulation of the essential cell cycle proteins Cyclin A, CKS1 and CDK1 [53] . Therefore, ROCK inhibition could open up a new spectrum for the removal of cellular senescence [ 32 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%